Cecum perforation by plug migration: an unexpected late complication of inguinal hernia mesh repair. Issue 3 (14th March 2023) - Policarpo, Filipa; Rafael, Ana Alves; Borges, Miguel Fróis; Azevedo, Fernando
Abstract: Case of a 79-year-old male previously submitted to Rutkow-Robbins inguinal hernia repair. He presented himself at the Emergency Room with an inguinal inflammatory mass and bowel obstruction for 5 days. A strangulated recurrent inguinal hernia was assumed and emergency surgery was performed. Since an inguinal abscess was present, a midline laparotomy was performed. The previous polypropylene plug was found in an intraperitoneal position, fistulizing to the cecum and creating a 2 cm wide perforation, without intraperitoneal collections or bowel compromise. An en bloc atypical resection of the cecum with the plug was performed and the abdominal wall abscess was drained. The patient had a slow, but uneventful postoperative course. Given the rarity of cases, the high variability of clinical presentation and the potential seriousness of mesh migration complications, the authors review the topic of mesh migration.